Modelling of acid brown 14 and acid yellow 36 dyes adsorption from water by self-nitrogen-doped activated carbon - Mohamed A. El-Nemr; Mohamed A. Hassaan; Murat Yılmaz; Ahmed El Nemr (Scientific Reports)
Abstract Acid Brown 14 (AB14) and Acid Yellow 36 (AY36) are synthetic azo dyes extensively utilized in numerous industries, resulting in detrimental environmental consequences. This study aims to manufacture self-nitrogen-doped porous activated carbon (AC7-800) and investigate its effectiveness in removing the AB14 and AY36 dyes from water solutions. The AC7-800 was created by combining fish waste (with a protein composition of 60% as a nitrogen source), which served as a self-nitrogen dopant. An equal mass ratio (1:1:1) of sawdust, fish waste, and zinc chloride underwent a hydrothermal treatment at 180 °C for 5 h. Subsequently, the material underwent pyrolysis for 1 h in a continuous flow of nitrogen gas at 800 °C to produce AC7-800. The AC7-800 adsorbent was successfully tested and approved to eliminate colours from water in batch trials. The AC7-800 samples were analyzed using BET, SEM, EDX, XRD, FTIR, TGA, and DTA techniques. The results demonstrated the practical synthesis of AC7-800 with a nitrogen mass percentage concentration of 13.73%. The specific surface area, mean pore diameter and monolayer volume were measured to be 437.51 m2 g− 1, 2.01 nm, and 100.52 cm3 g− 1, respectively. The objective is to examine the elimination of AB14 and AY36 dyes from a water-based solution using various factors such as initial dye concentration, solution pH, AC7-800 dosage, and contact time. The efficacy of AC7-800 in removing AB14 and AY36 dyes was found to be dependent on the pH level. The highest elimination efficiency of 63.29% and 85.86% was achieved at pH 1.5 for AB14 and AY36 dyes, respectively. Additionally, the maximum adsorption capacity (Q m ) for AB14 and AY36 dyes was determined to be 107.5 and 263.2 mg g− 1, respectively. The equilibrium data demonstrated a good association with the Langmuir model (LIM) for both dyes, although the best-fit kinetic model was the pseudo-second-order model (PSOM). Electrostatic interactions between the dye molecules and the charged spots on the AC7-800 surface cause both dyes to adsorb. The prepared AC7-800 can be considered a highly effective, accessible, and environmentally acceptable adsorbent for the adsorption of AB14 and AY36 dyes from simulated water. AB14 and AY36 dyes adsorption to AC7-800 was predicted by the response-surface methodology (RSM) and artificial neural networks (ANN) models. The ANN model was more effective in predicting AB14 and AY36 dyes adsorption than the D-optimal RSM, and it was highly applicable in the sorption process.